English First Additional Language teachers’ perceptions of translanguaging pedagogy : a case of Vhembe District, Limpopo Province - Ralushai, Mpfariseni M.; Ntombela, Berrington X.; Rammala, Johannes (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
This article reports on Grade 7 English First Additional Language (FAL) teachers’ perceptions of their use of a translanguaging pedagogy in teaching English FAL among Grade 7 learners in Vhembe District, Limpopo Province. The Continua of biliteracy model (CBM) underpinned the study. CBM foregrounds the development of biliteracy among bi/multilinguals and supports the view that learners’ communicative repertoires and language practices form an integral part of their learning process. The participants in the study were 6 Grade 7 English FAL teachers purposefully selected from three different primary schools. The study collected data through classroom observations, open-ended questionnaires, and semi-structured interviews. The overall results of the study revealed two differentiated strands of the teachers’ perceptions of the translanguaging approach in the teaching and learning of English FAL among Grade 7 learners. Firstly, the majority of Grade 7 teachers have a positive outlook on translanguaging pedagogy in the teaching and learning of English FAL. Alternation and flexible use of Tshivenḓa HL and English are permitted for scaffolding and acceleration of L2 learning. Secondly, the study revealed that some of these Grade 7 English FAL teachers objected to the use of translanguaging in preference for an English-only approach to accelerate the learning of English in their L2 classrooms. In their view, Tshivenḓa Home Language and English must be taught in isolation because of their distinct linguistic systems.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: English First Additional Language; Perceptions; Scaffolding; Second language; Translanguaging; Tshivenḓa Home Language; English language; Translanguaging (Linguistics); Venda language -- Study and teaching (Primary); Second language acquisition; English language -- Study and teaching